Effect of the presence of neomycin in goat’s milk on the making and characteristics of Tronchón cheese - Quintanilla P.; Beltrán M.C.; Palau B.; Escriche M.I.; Molina M.P. (Innovation for sustainability in sheep and goats, 2019)
Antibiotic residues in milk and dairy products are a potential problem for public health, and for the dairy industry. This study investigated the effect of the presence of neomycin in goat’s milk on the production and characteristics of semi-hard Tronchón cheese. Cheeses were made, in duplicate, from raw goat’s milk without antibiotics and with addition of neomycin at the Maximum Residue Limit (1500 μg/kg). Possible changes in the characteristics and the presence of antibiotic residues in the cheeses were evaluated at different time points along ripening (1, 30 and 60 days). Processing time was increased (48 ± 18 min) by the presence of neomycin in milk. Regarding cheeses, lower values of water activity as well as reduced free fatty acids and free amino-acid concentrations were detected in cheeses from milk with the antibiotic, suggesting a minor biochemical activity throughout ripening. Thus, a greater lightness and lower redness value were observed in this type of cheese, also presenting lower springiness. Moreover, high concentrations of neomycin were retained in the cheese and concentrated during ripening, leading to a concentration factor of 4.9, with respect to the initial concentration in the milk, potentially implying a risk to public health.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)